Competitiveness of private specialist medical entities in the opinion of service recipients - Dyjas, Wiktoria (Polish Journal of Public Health, 2020)
Introduction. The phenomenon of competitiveness and pressure of competitors that influence private medical institutions lead to the quest for new solutions on managing and defining determinants, which will provide advance of the institution over competing entities Aim. The purpose of the study was to determine factors influencing competitiveness of a medical institution according to the beneficiaries. Material and methods. The study group comprised 127 patients who used the services of private specialised medical institutions. Results and conclusions. The phenomenon of competitiveness in chosen types of medical services was noticed by 69% (88) of beneficiaries. High quality of services 79% (100), short waiting time for appointments 70% (89) and competitive prices 55% (70) are the main determinants of the competitiveness of those institutions.